2017
DOI: 10.3390/molecules22111873
|View full text |Cite
|
Sign up to set email alerts
|

Acaricidal Activity and Synergistic Effect of Thyme Oil Constituents against Carmine Spider Mite (Tetranychus Cinnabarinus (Boisduval))

Abstract: Studies examining the use of essential oils as replacements for synthetic insecticides require an understanding of the contribution of each constituent present, interactions among these components, and how they relate to overall toxicity. In the present study, the chemical composition of commercial thyme oil was identified by gas chromatography-mass spectrometry. Thyme oil and blends of its major constituents were tested for their acaricidal activitities against carmine spider mites (Tetranychus cinnabarinus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 46 publications
(54 reference statements)
0
15
0
Order By: Relevance
“…Hence, the joint actions of distinct binary mixtures of four terpenes were measured and ascertained the kinds of relations among them. According to Wu et al () and Abbassy et al () a CTF of +20 or more points to synergism, a value of −20 or less denotes antagonism, and values amid +20 and −20 mean an additive effect. Our study has shown that all the six binary combinations of four monoterpenes γ‐terpinene, R‐(+)‐limonene, carvacrol, and trans ‐anethole were exhibiting synergistic activity as the CTF was found to be > +20.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, the joint actions of distinct binary mixtures of four terpenes were measured and ascertained the kinds of relations among them. According to Wu et al () and Abbassy et al () a CTF of +20 or more points to synergism, a value of −20 or less denotes antagonism, and values amid +20 and −20 mean an additive effect. Our study has shown that all the six binary combinations of four monoterpenes γ‐terpinene, R‐(+)‐limonene, carvacrol, and trans ‐anethole were exhibiting synergistic activity as the CTF was found to be > +20.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is essential to know the type of chemical constituents contained in the EOs and their manner of action and their ratios and their mutual interactions (Pavela, ). The studies on the synergistic effect of the terpenes will be useful in two ways (Wu et al, ). First, this draw attention to the fact that the application of EOs as such as insect control agents will be more efficient than isolating the components for the same purpose and development of resistance can be curtailed by using the whole EO as such than purifying or chemical synthesis of their major constituents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an issue of social concern. Some studies found that essential oils had a more pronounced effect on pests compared with the effect of their major chemical component alone, because the oils showed antagonistic, additive, or synergistic effects in pest control . In this study, the effect between aliphatic acid and homoisoflavonoid destroyed the mid‐gut of S. litura more easily than other compounds singly (Fig.…”
Section: Discussionmentioning
confidence: 99%